Evolution of VRN-1 homoeologous loci in allopolyploids of Triticum and their diploid precursors - Andrey B. Shcherban; Elena A. Salina (BMC Plant Biology, 2017)
Abstract Background The key gene in genetic system controlling the duration of the vegetative period in cereals is the VRN1 gene, whose product under the influence of low temperature (vernalization) promotes the transition of the apical meristem cells into a competent state for the development of generative tissues of spike. As early genetic studies shown, the dominant alleles of this gene underlie the spring forms of plants that do not require vernalization for this transition. In wheat allopolyploids various combinations of alleles of the VRN1 homoeologous loci (VRN1 homoeoalleles) provide diversity in such important traits as the time to heading, height of plants and yield. Due to genetical mapping of VRN1 loci it became possible to isolate the dominant VRN1 alleles and to study their molecular structure compared with the recessive alleles defining the winter type of plants. Of special interest is the process of divergence of VRN1 loci in the course of evolution from diploid ancestors to wheat allopolyploids of different levels of ploidy. Results Molecular analysis of VRN1 loci allowed to establish that various dominant alleles of these loci appeared as a result of mutations in two main regulatory regions: the promoter and the first intron. In the diploid ancestors of wheat, especially, in those of A- genome (T. boeoticum, T. urartu), the dominant VRN1 alleles are rare in accordance with a limited distribution of spring forms in these species. In the first allotetraploid wheat species including T. dicoccoides, T. araraticum (T. timopheevii), the spring forms were associated with a new dominant alleles, mainly, within the VRN-A1 locus. The process of accumulation of new dominant alleles at all VRN1 loci was significantly accelerated in cultivated wheat species, especially in common, hexaploid wheat T. aestivum, as a result of artificial selection of spring forms adapted to different climatic conditions and containing various combinations of VRN1 homoeoalleles. Conclusions This mini-review summarizes data on the molecular structure and distribution of various VRN1 homoeoalleles in wheat allopolyploids and their diploid predecessors.